Upaya Peningkatan Pengetahuan Tentang Perilaku Seksual pada Siswa SMA Negeri 5 Surakarta melalui Video Animasi (Lembaga Pengembangan Kinerja Dosen, 2026)
Sexual behavior among adolescents is a reproductive health issue that can lead to various consequences, such as unplanned pregnancy, sexually transmitted infections, and the risk of dropping out of school. Technological developments and easy access to digital media also influence how adolescents obtain information and shape their attitudes and behaviors. Therefore, innovative, engaging educational media that align with the characteristics of younger generations are needed; one example is the use of animated videos. This community service activity aims to increase students' knowledge about sexual behavior through animated videos. The activity was held on May 6, 2024, at SMA Negeri 5 Surakarta, with 51 students in attendance. The methods used included interactive lectures, screenings of 3-minute 4-second animated videos, discussion sessions, and evaluations through pre- and post-tests. The evaluation results showed an increase in students' knowledge with an average score of 2.84 points. Thus, animated videos have proven effective in increasing adolescents' knowledge about sexual behavior and have the potential to be an engaging and educational health promotion medium.